INFLUENCIA DEL ARBOLADO Y MATORRAL EN EL CONTENIDO DE NITRÓGENO DEL PASTO HERBÁCEO EN LA DEHESA (PASTOS: FUENTE NATURAL DE ENERGÍA 4ª Reunión Ibérica de Pastos y Forrajes, 2010)
The objective of this assay is to analyse the influence of tree and shrub presence on nitrogen concentration in different herbaceous species. Two shrub species are studied: Cistus ladanifer L. Re- tama sphaerocarpa (L.) Boiss. In Spring 2009, different species of grass (Avena sativa L.), legumes (Ornithopus compresus L.) and Asteraceae (Senecio vulgaris L. and Taraxacum officinale (Lam.) Schrank), during flowering state. They were sampled in different positions respect to tree and shrub. Tree and R. sphaerocarpa presence improved pasture quality. C. ladanifer shrub reduced the pasture nitrogen content. Ornithopus compresus L. was the most affected specie to the different treatments. Key words: Pasture quality, Cistus ladanifer, Retama sphaerocarpa, Ornithopus compressus
The following values have no corresponding Zotero field: periodical: PASTOS: FUENTE NATURAL DE ENERGÍA 4ª Reunión Ibérica de Pastos y Forrajes